Once-monthly paliperidone palmitate in early stage schizophrenia – a retrospective, non-interventional 1-year study of patients with newly diagnosed schizophrenia - Emsley, Robin (Neuropsychiatr Dis Treat, 2017)
BACKGROUND: Long-acting antipsychotic therapy may be best suited for patients in the early stage of schizophrenia, when the most can be done before disease progression associated with poor adherence occurs. We explored the patterns of use of once-monthly paliperidone palmitate (PP1M), concomitant medication use, hospitalization, and clinical outcomes of adult, newly diagnosed patients with schizophrenia receiving continuous treatment with PP1M for at least 12 months. METHODS: This was an international, multicenter, exploratory, retrospective chart review of medical records of adult patients who were newly diagnosed (not more than 1 year before initiation of PP1M treatment) with schizophrenia and who had received continuous treatment with PP1M for ≥12 months in naturalistic clinical settings. RESULTS: A total of 84 (93.3%) patients were included in the analysis. All but one patient (98.8%, n=83) had received oral antipsychotic medication at least during the last month before the first PP1M administration. Three patients (3.6%) were newly hospitalized during the 12-month documentation period. The reason for hospitalization for all three was management of episode/relapse. A total of 79.2% of patients had a ≥20% improvement and 47.2% had a ≥50% improvement in Positive and Negative Syndrome Scale total score from baseline to endpoint. Half of patients (53.3%) showed a significant improvement, as reflected by an increase in Personal and Social Performance (PSP) total score of at least 7 points from baseline to endpoint (mean [SD] 11.9 [15.0] points; P<0.001). One quarter of patients (24.4%, n=11) moved from a PSP score of 31–70 (ie, moderate to marked functional impairment) at baseline to a PSP score of mild to no functional impairment (PSP score ≥71) at endpoint. Most adverse drug reactions were mild or moderate in severity. CONCLUSION: Continuous treatment with PP1M over 12 months was associated with statistically significant and clinically meaningful improvements in psychotic symptoms, disease severity, and functional outcomes in patients with schizophrenia.